Educational Tourism: Tribute to Fashion or New Educational Opportunities? - Zatsepina, Mariya B. (2020)
The relevance of this article lies in the need to study educational tourism as one of the ways to motivate students in educational process.  The article discusses new technologies in the educational process, which must be made more saturated and practically applicable. Visualization and the ability to implement the acquired knowledge can interest students and increase their interest in learning the information included in the curriculum. The purpose of the study is to analyze the importance of educational tourism for students. Research methods: As research methods, the following ones were used: questionnaire survey of participants of educational tours and free-style interviews with teachers and organizers of educational tourism, allowing identifying such characteristics of educational tourism’s value for students as awareness of participants about the project, previous personal experience, interest and satisfaction with the project. Research results: the article considers the importance of educational tourism from the point of view of its participants like students, accompanying teachers, from the point of view of the organizers of the tourist and educational project. The novelty and originality of the research lies in the fact that educational tourism is considered as an alternative to educational activities, which allows not only to make a trip, but also to acquire new knowledge, skills and abilities during it, which will be learned much better than just memorizing the material from the book. It is shown that the value of educational tourism can be assessed if there is knowledge about its components such as interest and personal experience of its participants, satisfaction or dissatisfaction with certain elements of the educational tour, awareness of the project possibilities, features of the organization and implementation of the tour. It is revealed that educational tourism performs not only directly educational, but also socially significant functions for society. The study shows that the project participants perceive the educational component easily and without difficulties and there is a high interest of students in educational tours. It is revealed that the accompanying notes a positive dynamic in the interest in the educational process after participation in the project. Both its participants and its organizers perceive the possibility of expanding the project positively. It is determined that the greatest difficulty in the organization of educational tourism is caused by the lack of support of state structures, which in turn causes difficulty in entering new sites where the project can be implemented. It is shown that the educational component of the project is positively evaluated by both direct consumers and teachers in terms of the correctness in the construction of the narrative and semantic parts. It is shown that to the positive aspects of educational tourism can be attributed the emotional involvement of participants in the educational process during the excursion service, as well as increasing the level of their interest in further study. Practical significance: the data obtained in this work can be used in social psychology, pedagogy, age psychology, pedagogical psychology, as well as for further theoretical development of this issue.